Single page letter to William Hone from Thomas J. Wooler, no date. - Wooler, T. J. 1786?-1853 (Thomas Jonathan); Hone, William, 1780-1842
This letter seems to confirm the journalist Thomas J Wooler's active involvement in the Cato Street Conspiracy of February 1820 to assassinate the British cabinet. For further details see Jason McElligott & Martin Conboy (eds), The Cato Street Conspiracy: Plotting, counter-intelligence and the revolutionary tradition in Britain and Ireland (Manchester, 2020), chapter 3.
Roger Collicott Books
Unbound